BREAKING DORMANCY IN IPE-YELLOW SEEDS (Tabebuia vellosoi) WITH THE USE OF WATER: THE BEST TIME EVALUATION. - Biagolini, Carlos Humberto [UNESP]; Nascimento Lopes, Elfany Reis do [UNESP]; Watanabe, Claudia Hitomi [UNESP]; Frascareli, Daniele [UNESP]; Kumazawa, Vinicius R. [UNESP] (Faema-fac Educacao & Meio Ambiente, 2016)
The Tabebuia vellosoi popularly known as Ipe-Yellow is a Brazilian plant, typical of open formations of the rain forest from the top of the rainforest, but with good development also in regions with savannah characteristics. It is considered a symbol tree of Brazil. Reproduction can be by cuttings or seeds that require breaking dormancy to obtain better germination rates, which sometimes becomes problematic due to differences in how to proceed. In the literature, quotes were found in which indicate periods and 12 h, 18 h, 24 h and 60 hours of immersion in water before planting. This research aimed to evaluate the best period to break dormancy. The results indicate that the seeds subjected to 18 hours break dormancy showed the best results in both the number of germinated seeds as well as the initial length of the roots comparing yourself with other periods, facilitating even after bud break, the replanting in plastic bags suitable for seedlings to replant in open field.
Keywords: Ipe-Amarelo; Ornamental Plants; Urban Reforestation